Age at Smoking Initiation in Slovenia - KOPRIVNIKAR, Helena (Zdr Varst, 2015)
BACKGROUND: Smoking is initiated mostly by adolescents and young adults. In Slovenia, we have limited data about this. The purpose of this paper is to show data on age at smoking initiation and differences in age at smoking initiation by gender, age groups, education, social class and geographical region among inhabitants of Slovenia. METHODS: We used data from the cross-sectional survey ‘Health-related behaviour 2012’ in Slovenian population aged from 25 to 74 years. RESULTS: 4591 ever smokers, aged 25–74, that gave information about the age at smoking initiation were included in the analysis. At the age of 25 or less, smoking was initiated by 96.7% of Slovene ever smokers, at the age of 18 or less by 71.0%. The average age at smoking initiation was 17.7 years. Male ever smokers initiated smoking at an earlier age compared to female ones. Age at smoking initiation was decreasing in both male and female ever smokers, but was more pronounced in females. In male ever smokers, there were no differences in average smoking initiation age by education, self-reported social class and geographical regions, while in female ever smokers, there were significant differences in terms of education and geographical regions. CONCLUSION: The initiation of smoking predominantly occurs in adolescents and young adults. Age at smoking initiation has decreased in recent decades. Our study confirms the importance of early and sustained smoking prevention programmes in youth and the importance of national comprehensive tobacco control programme with effective tobacco control measures to ban tobacco products marketing.